Strategies at SMP Muhammadiyah 9 Tanggulangin Boarding School in Online and Offline Learning During the Covid-19 Pandemic - Faradila Putri; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study aims to determine the process of online learning and offline learning during the covid-19 pandemic at SMP Muhammadiyah 9 Tanggulangin Boarding School. The research method used is a qualitative method. Methods of collecting data by conducting interviews with one of the teachers who teach at the school. There are two kinds of learning carried out by SMP Muhammadiyah Tanggulangin, namely online learning and offline learning. Online learning began to be implemented when the government issued a warrant to study at home. However, in June 2020 the school decided to continue offline learning. This learning has special requirements so that students can enter school offline again. Until now, offline and online learning can run in a conducive and orderly manner.